Hubungan Antara Konsep Diri dan Regulasi Diri terhadap Tingkat Prokrastinasi Mahasiswa Pendidikan Agama Islam - Efrida Mandasari; Muhammad Ihsan (IAIN Padangsidimpuan, 2020)
This study aims to determine the relationship between self-concept and self-regulation with procrastination in student. This research uses correlational quantitative desigan. The sample used amounted 77 of the population 729 student with purposive sampling technique. The data analysis technique with multiple regression . The results showed that a positive relationship between the self- concept and self-regulation was positively linked to the procratation of students. This is indicated by the coefficient of Freg = 58,654 where p 0.05. This indicates that self-concept and self-regulation are significantly linked to academic procrastination, the higher the value of self-concept and self-regulation, the lower the academic procrastination. Conversely, the lower the value of self-concept and self-regulation, the higher the academic procrastination.